Quick-hardening high-strength cement anchoring agent and strength testing method thereof
By adjusting the raw material composition and additive ratio of the anchoring agent, the problems of difficult to control the settling time of the anchoring agent during use, poor crack resistance, and insufficient early strength are solved, and the strength of the anchoring agent is achieved in combination with piezoelectric impedance technology and LSTM. Real-time non-destructive monitoring to meet the construction needs of complex engineering environments.
Patent Information
- Application Number
- CN202411519526.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-29
AI Technical Summary
During use, existing anchoring agents have problems such as difficult to control the settling time, poor cracking resistance, insufficient early strength and uneven expansion, and it is difficult to monitor the strength of the anchoring agent in real time and accurately.
By changing the raw material composition and additive ratio of anchoring agent, adjusting the settling time, improving crack resistance and early strength, and using a combination of piezoelectric impedance technology and long-term memory network (LSTM) to achieve real-time non-destructive monitoring of anchoring agent strength .
The rapid condensation, high early strength, good crack resistance and micro-expansion characteristics of anchoring agent are achieved, which meets the construction needs of complex engineering environments and improves the efficiency and accuracy of strength monitoring.
Smart Images

Figure CN119462028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tunnel construction materials and detection, and in particular to a fast-hardening high-strength cement anchoring agent and a strength testing method thereof. Background Art
[0002] At present, China's railway and highway construction is gradually advancing towards the central and western regions. However, with the continuous uplift of the Qinghai-Tibet Plateau and its squeezing effect on the eastern region, the geological structure, hydrogeological conditions and stratigraphic complexity in southwest China have increased significantly, and the distribution of fault fracture zones is particularly dense. This complex geological environment, accompanied by the rapid development of infrastructure construction in the southwestern mountainous areas, makes tunnel engineering more frequent and challenging when crossing highly active fault areas. Fault fracture zones are usually composed of broken rocks and loose soil, with loose overall structure and poor stability, which can easily cause a series of engineering disasters such as large-scale deformation of tunnel support structures and face collapse. In addition, these geological risks pose a severe test to the safety of engineering construction and the long-term stability of later structures. In order to effectively deal with the problem of large deformation of soft rock tunnels, experts in related fields have proposed a variety of innovative support strategies based on different design concepts, mainly including fast and effective strong support, layered multiple support and other methods.
[0003] Anchors are mainly used to reinforce rocks and soil in tunnel construction to ensure the structural stability of the tunnel. Its working principle is to inject anchors (such as cement-based or chemical-based anchors) into the borehole. After the anchor solidifies, the anchor rod or other structure is firmly bonded to the surrounding rock or soil, thereby providing support and pull-out resistance. Through chemical reactions or physical hardening processes, the anchor forms a strong bond with the surrounding medium to achieve the effect of stabilization and reinforcement. Chemical anchors use epoxy resin or polyester resin as the main component, in which amine compounds are added as curing agents to promote resin curing. The advantages of chemical anchors are that they are resin anchors with fast solidification speed and are suitable for projects that require rapid reinforcement; they have strong bonding with rock mass and can withstand large pull-out forces, making them suitable for anchoring weak surrounding rock or unstable rock mass. The disadvantages of chemical anchors are that epoxy resins are expensive and have high costs; chemical gases may be produced during the curing process, which poses health and environmental risks; and the resin is prone to aging and decomposition in high temperature or corrosive environments, and has poor durability. Cement-based anchors are usually composed of aggregates such as silicate cement or high-alumina cement, quartz sand or fine sand, admixtures for adjusting the setting time and enhancing fluidity (such as water reducers, early strength agents), and water, and promote hardening through hydration reactions. Its advantages include low cost, easy access to materials, good corrosion resistance and long-term durability, and relative environmental protection, and no harmful substances are produced during construction. However, the setting time of cement-based anchors is long, which makes it difficult to meet the requirements of rapid construction, and the curing effect may be affected in low temperature or humid environments, and the fluidity is poor, which may lead to uneven anchoring. Due to the advantages of chemical anchors, they are widely used in tunnel construction in mountainous areas in southwest my country. However, the geological, hydrogeological and stratigraphic conditions in the area are extremely complex, and resin chemical anchors have poor durability and are prone to aging and decomposition. Therefore, it is necessary to provide a fast-hardening high-strength cement anchor to better meet the requirements of immediate strong support in tunnel projects in mountainous areas in southwest my country and the requirements of operation in complex environments with high temperature, high ground stress and high degree of groundwater development.
[0004] Rapid hardening high-strength cement anchor is a typical cement material. Cement materials are widely used in civil engineering and play an irreplaceable role throughout the construction industry. The early hydration and solidification of cement involve complex physical and chemical reactions between clinker minerals and water, which are crucial to the performance of cementitious materials such as cement and cement mortar. This process directly determines the formation of microstructure and affects the physical, mechanical and durability properties of cement hydrates after hardening. For engineers, continuous monitoring and evaluation of the early hydration and solidification process of cement is necessary because it can provide key construction information, help determine the best time to demold or remove temporary supports, and minimize unnecessary delays in the construction cycle. Real-time monitoring can also determine the hardening state of cement. There are many destructive and non-destructive testing methods (NDT), such as conventional Vicat needle penetration test, isothermal calorimetry and hydration condition monitoring, but the current detection methods have the disadvantages of being unable to achieve continuous measurement, low accuracy, complex equipment, and difficult operation. Therefore, developing a reliable, real-time, autonomous and intelligent non-destructive strength testing method for fast-hardening high-strength cement anchors is crucial for accurately monitoring and evaluating the early hydration and setting process of the material. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a fast-hardening high-strength cement anchor and a strength testing method thereof, aiming to solve the problems of insufficient durability, slow setting time, poor early strength of the existing anchor and difficulty in real-time and accurate monitoring of the anchor strength by the existing methods.
[0006] In order to solve the problems of difficult-to-control setting time, poor crack resistance, insufficient early strength and uneven expansion of existing anchoring agents during use, the present invention successfully adjusts the setting time of the anchoring agent by changing the raw material composition and additive ratio of the anchoring agent, improves the crack resistance, and maintains a small expansion coefficient, and greatly improves the early strength and anchoring force to meet the construction needs of complex engineering environments. A fast-hardening high-strength cement anchoring agent of the present invention includes the following raw materials by mass fraction: 50% to 70% sulphoaluminate cement, 10% to 20% silica fume, 10% to 20% desulfurized gypsum, 3% to 10% expansion agent, 0.05% to 0.3% composite retarder, 0.01% to 0.1% early strength agent, and 0.02% to 0.1% defoamer.
[0007] The main components of the sulphoaluminate cement are calcium sulphoaluminate and gypsum.
[0008] The core component of the present invention is sulphoaluminate cement, which occupies a dominant position in anchoring agents due to its characteristics of rapid coagulation and high early strength. Its main components are calcium sulphoaluminate and gypsum, which can quickly generate hydration products with high strength in the hydration reaction, thereby accelerating the coagulation process of the anchoring agent and significantly shortening the construction period. At the same time, the use of sulphoaluminate cement also makes the anchoring agent show high compressive strength in the early stage, ensuring that an effective anchoring effect is quickly formed in engineering construction.
[0009] In order to further improve the performance of the anchoring agent, the present invention also introduces 10% to 20% silica fume. Silica fume is an ultrafine mineral admixture with fine particles and large specific surface area. It can act as a filling material in the anchoring agent to fill the tiny pores in the cement matrix and enhance the density and durability of the anchoring agent. At the same time, the addition of silica fume can also significantly improve the crack resistance of the anchoring agent, because silica fume can generate additional gelling substances with cement hydration products, reduce the occurrence of shrinkage cracks, and enhance the overall crack resistance of the material.
[0010] Desulfurized gypsum as a regulating material also occupies an important position in the present invention. Its dosage is controlled at 10% to 20%. By adding desulfurized gypsum, not only the early strength of the anchor can be further improved, but also the expansion performance can be adjusted. During the hydration reaction, desulfurized gypsum can work together with sulfoaluminate cement to generate hydration products with expansion properties, thereby controlling the volume change of the anchor, so that it maintains a slightly expanded state during the coagulation process, avoiding the generation of excessive shrinkage cracks. In addition, the use of desulfurized gypsum can also effectively adjust the coagulation time of the anchor, ensuring better operability during the construction process.
[0011] The expansion agent is also an important component of the present invention, and its dosage is controlled between 3% and 10%. The main function of the expansion agent is to produce an appropriate amount of expansion during the hydration process of the anchoring agent, offset the stress caused by the shrinkage during the cement hardening process, and prevent the anchoring agent from cracking after solidification. The preferred expansion agent type is at least one of calcium oxide, sulphoaluminate and magnesium oxide expansion agents. Through a reasonable expansion agent ratio, the anchoring agent has micro-expansion characteristics while maintaining high strength, thereby enhancing the anchoring effect.
[0012] In order to delay the setting time of the anchoring agent, the present invention adopts 0.05% to 0.3% of a composite retarder, and the preferred composite retarder is a combination of sucrose-citric acid, or a combination of borax and sodium citrate. These retarders can effectively prolong the setting time of cement and ensure sufficient operation time during the construction process. Especially when sulphoaluminate cement has a faster setting speed, the use of a retarder is particularly important, which can balance the rapid setting characteristics of the material and make the anchoring agent have better construction adaptability.
[0013] In the selection of early strength agent, the present invention particularly adopts 0.01% to 0.1% ethylene glycol. Ethylene glycol is a commonly used early strength agent, which can significantly improve the early strength of the anchoring agent by accelerating the hydration reaction process of cement. In the preparation of the anchoring agent, the use of lithium carbonate ensures that the anchoring agent reaches the required strength level in a short time, meeting the high requirements of the project for early strength. At the same time, the addition amount of ethylene glycol is precisely controlled, which not only ensures the early strength effect, but also avoids the negative effects that may be caused by excessive addition, such as material embrittlement.
[0014] The defoamer in the present invention plays the role of removing air and improving the density of the material. The dosage of the defoamer is controlled between 0.02% and 0.1%. By adding an appropriate amount of the defoamer, the bubble content in the anchoring agent can be effectively reduced, and pores can be prevented from appearing inside the material, thereby improving the overall density and mechanical properties of the anchoring agent.
[0015] After the components in the present invention are scientifically proportioned, the anchoring agent can achieve the comprehensive effects of adjusting the setting time, enhancing the anti-cracking performance, maintaining micro-expansion and improving the early strength. Among them, sulphoaluminate cement is the basic cementitious material, silica fume and desulfurized gypsum play the role of improving density, adjusting expansion and improving the setting time, ethylene glycol as an early strength agent ensures the rapid strength growth of the anchoring agent, and the retarder and defoamer further optimize the construction performance of the material.
[0016] On the other hand, as an innovation in concrete strength monitoring technology, the present invention combines long short-term memory network (LSTM) and piezoresistive impedance technology for fast strength monitoring of high-strength cement anchors. This method is based on the electromechanical coupling characteristics of piezoelectric ceramics (PZT) and the time series data processing capabilities of LSTM neural networks. By acquiring piezoresistive impedance data and training the neural network model, real-time and non-destructive monitoring of the strength of the anchor is achieved. To achieve the above purpose, the present invention also provides the following technical solution: A strength test method for fast-hardening high-strength cement anchors, comprising the following steps:
[0017] S1: Collect the piezoresistive impedance signal data of cement anchor through piezoelectric ceramic sensor;
[0018] S2: The rebound method collects the actual strength data of cement anchor at different strength stages;
[0019] S3: preprocess the piezoelectric impedance signal dataset and the intensity dataset, and construct a time series dataset;
[0020] S4: Use the long short-term memory network LSTM to train the model, learn the relationship between the piezoresistive impedance signal and the strength, and establish a cement anchor strength prediction model;
[0021] S5: Validate and optimize the model;
[0022] S6: Apply the optimized model to actual projects to achieve real-time nondestructive monitoring of cement anchor strength.
[0023] Preferably, in step S3, the following is specifically included:
[0024] S301: preprocessing the piezoelectric impedance signal, including performing empirical mode decomposition (EMD) and Hilbert transform (HHT) on the signal to extract the instantaneous amplitude;
[0025] S302: Divide the processed signal data set into a training set and a validation set in proportion;
[0026] S303: Label the data set to ensure that each signal data corresponds to the corresponding cement anchor strength.
[0027] Preferably, in step S5, the following is specifically included:
[0028] S501: Input the validation set into the trained model for prediction;
[0029] S502: using a loss function to compare the intensity prediction result output by the model with the actual intensity;
[0030] S503: Based on the comparison results, the weight parameters and network topology of the LSTM network are adjusted to optimize the model performance.
[0031] Preferably, in step S502, the mean square error MSE is used as a loss function to measure the error between the network predicted strength value and the true strength value, and the formula is as follows:
[0032]
[0033] Among them, y i is the actual strength, Predict strength for the model.
[0034] The beneficial effects of the present invention are as follows: the present invention provides a quick-setting cement anchor with excellent performance by rationally proportioning sulphoaluminate cement, silica fume, desulfurized gypsum and various additives. The anchor not only has the advantages of rapid coagulation and high early strength, but also has good anti-cracking performance, micro-expansion characteristics and operational adaptability, and can be applied in a variety of complex engineering environments to meet the high standards required in actual construction. By combining piezoelectric impedance technology and LSTM neural network, the present invention can automatically extract the time series characteristics of the strength of cement anchors, realize fast and accurate non-destructive testing, greatly improve the efficiency and accuracy of strength monitoring, and once an abnormality is detected, timely warning and remedial measures can be taken. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic flow chart of a strength testing method of a fast-hardening high-strength cement anchoring agent of the present invention;
[0036] Figure 2 This is a schematic diagram of the piezoelectric impedance principle of the present invention;
[0037] Figure 3 This is a schematic diagram of the long short-term memory network LSTM of the present invention;
[0038] Figure 4 Schematic diagram of the test device for collecting piezoresistive impedance signals of cement anchoring agents using the piezoelectric ceramic sensor of the present invention. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] The present embodiment provides a fast-hardening and high-strength cement anchor, comprising the following raw materials: 50wt% sulphoaluminate cement, 15wt% silica fume, 15wt% desulfurized gypsum, 7wt% expansion agent, 0.2wt% composite retarder (sucrose and citric acid prepared in a mass ratio of 4:1), 0.1wt% early strength agent, and 0.05wt% defoaming agent.
[0042] The preparation method is as follows: silica fume and desulfurized gypsum are mixed with water in a mass ratio of 1:100, stirred at 1000 rpm for 5 minutes, then sulphoaluminate cement is added, stirred at 5000 rpm for 5 minutes, and then anhydrous ethanol is added and stirred at 5000 rpm for 4 minutes to obtain a modified mineral admixture dispersion. The modified mineral admixture is dried at 110°C and ground to a particle size not exceeding 20 μm. The mass ratio of silica fume to water is 100:3, and the mass of anhydrous ethanol is 20wt% of water.
[0043] The composite retarder is prepared by sucrose and citric acid in a mass ratio of 4: 1. Sulphoaluminate cement, silica fume, desulfurized gypsum, expansion agent, composite retarder, early strength agent and defoamer are mixed evenly, packed into a packaging bag with a diameter of 33 mm, and made into a cylindrical anchoring bag to form a quick-setting cement anchoring agent.
[0044] Example 2
[0045] The present embodiment provides a fast-hardening and high-strength cement anchor, and the raw materials used include: 60wt% sulphoaluminate cement, 12wt% silica fume, 13wt% desulfurized gypsum, 6wt% expansion agent, 0.15wt% composite retarder (sucrose and citric acid prepared in a mass ratio of 4.5:1), 0.08wt% early strength agent, and 0.03wt% defoaming agent.
[0046] The preparation steps are as follows: silica fume and water are mixed in a mass ratio of 1:100, stirred at 1200 rpm for 4 minutes, then sulphoaluminate cement is added, stirred at 5000 rpm for 5 minutes, and then anhydrous ethanol is added and stirred for 4 minutes to obtain a modified mineral admixture dispersion, which is dried at 110°C and ground to a particle size of no more than 20 μm. The ratio of water to ethanol is 100:3, and ethanol accounts for 20 wt% of the mass of water.
[0047] The composite retarder is prepared from sucrose and citric acid in a mass ratio of 4.5:1. Sulphoaluminate cement, silica fume, desulfurized gypsum, expansion agent, composite retarder, early strength agent and defoamer are mixed and packed into a packaging bag to form a cylindrical anchor bag with a diameter of 35 mm.
[0048] Example 3
[0049] The fast-hardening high-strength cement anchor of this embodiment includes the following raw materials: 55wt% sulphoaluminate cement, 10wt% silica fume, 20wt% desulfurized gypsum, 0.07wt% lithium carbonate, 5wt% expansion agent, 0.1wt% composite retarder (borax and sodium citrate prepared in a mass ratio of 10:1), 0.1wt% ethylene glycol, and 0.02wt% defoaming agent.
[0050] The preparation method is as follows: silica fume and water are mixed in a mass ratio of 1:100, stirred at 1000 rpm for 5 minutes, sulphoaluminate cement is added and stirred at 5000 rpm for 5 minutes, anhydrous ethanol is added and stirred for 4 minutes to obtain a modified mineral admixture dispersion. After drying at 110°C, the dispersion is ground to a particle size of no more than 20 μm.
[0051] The composite retarder is made of borax and sodium citrate in a ratio of 10:1. All raw materials are mixed evenly in proportion to form an anchor package with a diameter of 33 mm.
[0052] Example 4
[0053] The fast-hardening and high-strength cement anchor provided in this embodiment includes the following raw materials: 70wt% sulphoaluminate cement, 10wt% silica fume, 10wt% desulfurized gypsum, 0.05wt% lithium carbonate, 4wt% expansion agent, 0.2wt% composite retarder (sodium phosphate and phosphoric acid are prepared in a mass ratio of 4:1), 0.02wt% early strength agent, and 0.05wt% defoaming agent.
[0054] The preparation method is as follows: silica fume and water are mixed in a mass ratio of 1:100, stirred at 1000 rpm for 5 minutes, sulphoaluminate cement is added and stirred at 5000 rpm for 5 minutes, anhydrous ethanol is added and stirred for 4 minutes to obtain a modified mineral admixture dispersion, which is dried and ground to a particle size of no more than 20 μm. The mass of the ethanol is 20 wt% of the water.
[0055] Mix all the raw materials evenly in proportion and make a cylindrical anchor package with a diameter of 33mm for construction anchoring.
[0056] Comparative Example 1
[0057] The composition of the quick-setting cement anchor provided in this comparative example is the same as that of Example 1, except that no desulfurized gypsum is added. After testing, it was found that this ratio resulted in a significant shortening of the initial setting time of the anchor, a 1-hour compressive strength of 25.4 MPa, and a decrease in expansion performance.
[0058] Silica fume and water were mixed at a mass ratio of 1:100, stirred at 1000 rpm for 5 minutes, then sulphoaluminate cement was added, stirred at 5000 rpm for 5 minutes, and then anhydrous ethanol was added and stirred at 5000 rpm for 4 minutes to obtain a modified mineral admixture dispersion. The modified mineral admixture was dried at 110°C and ground to a particle size of no more than 20 μm.
[0059] Comparative Example 2
[0060] The composition of the quick-setting cement anchor provided in this comparative example is the same as that of Example 2, except that no composite retarder is added. The test results show that the initial setting time is greatly shortened to 2:30 without the addition of the composite retarder, and the 1-hour compressive strength is 22.1 MPa. Too fast setting time affects the construction adaptability.
[0061] Comparative Example 3
[0062] The composition of the quick-setting cement anchor provided in this comparative example is the same as that of Example 3, except that ethylene glycol is not used as an early strength agent. The test results show that the initial setting time is extended to 8:15 without the addition of ethylene glycol, and the 1-hour compressive strength decreases to 18.7 MPa, and the early strength is obviously insufficient.
[0063] Comparative Example 4
[0064] The composition of the quick-setting cement anchor provided in this comparative example is the same as that of Example 4, except that no expansion agent is added. The test results show that when no expansion agent is added, the expansion performance of the anchor is significantly reduced, and the 28-day expansion rate is only 0.015%, and the 1-hour compressive strength is reduced to 20.9Mpa, as shown in Table 1.
[0065] Table 1 Performance comparison between the examples and the comparative examples
[0066]
[0067] As can be seen from Table 1, compared with the embodiment, although the main components are the same in Comparative Example 1, the initial setting time is shortened due to the lack of desulfurized gypsum, and the 0.5 hour and 1 hour compressive strengths are also significantly reduced, showing that the setting time is too fast and is not conducive to construction operations. Comparative Example 2 does not add a composite retarder, resulting in an initial setting time that is too short, and the 1-hour compressive strength is also significantly reduced. The excessive setting speed affects the stability and strength performance of the material. In Comparative Example 3, no early strength agent is used, the initial setting time is greatly extended, the early strength performance is poor, and the compressive strength is significantly lower than that of the embodiment, reflecting the importance of lithium carbonate in improving early strength. Comparative Example 4 does not add an expansion agent. Although the initial setting time is extended, the expansion performance is significantly reduced, and the 0.5 hour and 1 hour compressive strengths are significantly reduced, affecting the overall performance of the material.
[0068] In summary, the formula in the embodiment optimizes the setting time and early strength of the anchor through a reasonable material ratio, ensuring the comprehensive performance of the material, while the different formula adjustments in the comparative examples all have a negative impact on the performance of the anchor. Therefore, balancing the setting time and compressive strength and maintaining a reasonable ratio of each component in the formula are the key to ensuring the performance of the anchor.
[0069] A strength test method for a fast-hardening high-strength cement anchoring agent, wherein the fast-hardening high-strength cement anchoring agent used in the test method is prepared according to the formula in Example 1, such as Figure 1 As shown, the method comprises the following steps:
[0070] S1: Collecting piezoresistance signal data of cement anchors through piezoelectric ceramic sensors
[0071] Specifically, lead zirconate titanate piezoelectric ceramics (PET) are used as intelligent sensors to test the fully stirred fast-hardening high-strength cement anchor in the standard column mold to obtain a signal spectrum in a specified frequency range. Alternatively, a PZT sensor is attached to the surface of the cement anchor, and the conductivity and impedance data of the anchor at different strength stages are collected by an impedance analyzer to obtain a time domain signal. A piezoelectric ceramic sensor is used to collect the piezoresistance impedance signal test device of the cement anchor, such as Figure 4 As shown. Signal data acquisition specifically includes the following:
[0072] S101: Prepare the fast-hardening high-strength cement anchor according to the above standards, use an electric mixer to fully stir the anchor mixture, and then pour the fresh mortar into a standard prism mold with a size of 60.0×60.0×170.0 mm.
[0073] S102: EMI measurement uses a circular raw PZT patch with a diameter of 19.8 mm and a thickness of 1.0 mm. Before the actual application of the PZT patch as an impedance sensor, it is completely covered with a thin film of dielectric and water-resistant coatings and two wires are soldered on its electrodes.
[0074] S103: Immediately after the mixed mortar was made, a fine PZT sensor was mounted at the center of the test sample and aligned longitudinally with the prism mold, using a homemade wooden strip to assist in the precise positioning of the sensor.
[0075] S104: EMI measurements were performed using an Agilent 4294A impedance analyzer with excitation frequencies ranging from 40.0 Hz to 110.0 MHz.
[0076] S105: In each measurement, the EMI spectra of two different frequency ranges were measured, namely 0-1000kHz and 0-3000kHz, corresponding to the d31 and d33 resonance modes of the piezoelectric sensor, respectively. The EMI test of the PZT sensor was performed every 10 minutes before the mortar reached final solidification. After that, the impedance signal was collected every hour during the hydration and solidification process of the mortar at the early age, for a total of 72 hours.
[0077] Principle of Piezoresistive Technology
[0078] like Figure 2 As shown in the figure, the piezoelectric effect is divided into the positive piezoelectric effect and the inverse piezoelectric effect. The positive piezoelectric effect refers to the generation of electric charge by the piezoelectric material under the action of mechanical force, while the inverse piezoelectric effect refers to the deformation of the piezoelectric material under the action of an electric field. Using this characteristic, piezoelectric ceramics can be used as both drivers and sensors. When an alternating voltage is applied to the PZT, it drives its vibration and transmits the vibration to the cement anchor structure being tested; in turn, the mechanical impedance of the anchor structure changes the vibration response of the PZT, which is reflected in the changes in the conductivity and impedance of the piezoelectric sheet.
[0079] The electric displacement of PZT in the coupled system is:
[0080]
[0081] Calculate the current:
[0082] I=iω∫∫D3dxdy
[0083] Where:
[0084]
[0085] Furthermore, considering that in most cases the experimental frequency is well below the resonant frequency of PZT:
[0086]
[0087] The formula of PZT's coupled electrical admittance can be simplified as:
[0088]
[0089] More specifically, the electrical conductance (Y) of PZT is related to the mechanical impedance of the anchor as follows:
[0090]
[0091] Where ω is the angular frequency of the excitation signal, C0 is the baseline capacitance of the PZT, and Z S is the mechanical impedance of the anchor, Z A is the mechanical impedance of PZT.
[0092] S2: The rebound method collects the actual strength data of cement anchors at different strength stages. The details include the following:
[0093] S201: Identify areas on the concrete surface that are clean, flat, and free of obvious defects as test points. Each test area should be distributed with 10 to 12 test points to avoid repeated testing at the same location on the concrete surface.
[0094] S202: Clean the test point and ensure that there is no dust, coating, oil or other substances that may affect the rebound value. If the concrete surface is rough or has loose materials, gently polish it with sandpaper or grinding stone to ensure it is flat and smooth.
[0095] S203: Before the formal test, ensure that the Schmidt rebound hammer is calibrated. Calibration should be performed on a standard hardness block that meets the requirements to ensure that the equipment is in normal working condition.
[0096] S204: Place the rebound hammer in vertical contact with the concrete surface, apply pressure gently, keep the rebound hammer stable and close to the surface, quickly press the trigger device to release the impact force, and the instrument will automatically record the rebound value. Perform multiple tests in the same area (usually more than 10 times) and record the rebound value of each test point.
[0097] S205: Calculate the average rebound value of each test area.
[0098] S206: Repeat steps S201-S205 at fixed intervals Δt, determine the standard rebound strength curve for cement anchors (provided by the instrument or with reference to relevant specifications) based on the change in the average rebound value over time, and convert the measured rebound average value into a concrete strength value.
[0099] S3: Preprocess the piezoelectric impedance signal data set and the intensity data set, and construct a time series data set. Specifically including:
[0100] S301: Preprocessing the piezoelectric impedance signal, including performing empirical mode decomposition (EMD) and Hilbert transform (HHT) on the signal to extract the instantaneous amplitude; obtaining an instantaneous amplitude data set of the conductance.
[0101] Mathematically, the instantaneous amplitude of the Hilbert transform can be expressed as:
[0102]
[0103] Among them, y(t) is the original signal, is its Hilbert transform.
[0104] S302: Divide the processed signal data set into a training set and a validation set in proportion;
[0105] S303: Label the data set to ensure that each signal data corresponds to the corresponding cement anchor strength.
[0106] S4: Use the long short-term memory network (LSTM) for model training, learn the relationship between piezoresistive impedance signals and strength, and establish a cement anchor strength prediction model.
[0107] like Figure 3 As shown in Figure 1, the long short-term memory network (LSTM) is used to process time series data, such as the change of piezoelectric impedance signals over time. LSTM is suitable for extracting complex time series features of piezoelectric impedance data by memorizing past states and handling long-term dependencies. The specific network structure is expressed by the following formula:
[0108] The calculation formula of LSTM unit is:
[0109] f t =σ(W f ·[h t-1 ,x t ]+b f )
[0110] i t =σ(W i ·[h t-1 ,x t ]+b i )
[0111]
[0112] o t =σ(W o ·[h t-1 ,x t ]+b o )
[0113] h t =ot *tanh(C t )
[0114] Among them, f t is the forget gate, which controls how much historical information is discarded; i t is the input gate, which determines the memory level of the current information; C t is the unit state; o t It is the output gate, which ultimately determines the output.
[0115] The collected instantaneous amplitude data set is input into the LSTM network for training. The network input is time series data, and the output is the strength prediction value of the cement anchor. The LSTM network learns the complex nonlinear relationship between the piezoresistive impedance signal and the anchor strength through multiple iterations.
[0116] S5: Verify and optimize the model; specifically include the following:
[0117] S501: Input the validation set into the trained model for prediction;
[0118] S502: using a loss function to compare the intensity prediction result output by the model with the actual intensity;
[0119] The mean square error (MSE) is used as the loss function to measure the error between the network predicted strength value and the true strength value. The formula is as follows:
[0120]
[0121] Among them, y i is the actual strength, Predict strength for the model.
[0122] S503: Based on the comparison results, adjust the weight parameters and network topology of the LSTM network to optimize the model performance. Ensure its learning ability for piezoelectric impedance data. Evaluate the network performance through the validation set. If the accuracy and recall rate reach the expected effect, stop the optimization.
[0123] The test data that was not involved in the training was input into the model, and the strength value predicted by the calculation model was compared with the actual measured anchor strength value to verify the accuracy and generalization ability of the model. The model can be further optimized by adjusting the network parameters (such as learning rate and number of layers).
[0124] S6: Apply the optimized model to actual projects to achieve real-time non-destructive monitoring of cement anchor strength. Collect data through PZT sensors and input into LSTM networks to automatically predict the strength value of cement anchors to ensure construction quality and safety.
[0125] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0126] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0127] The word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining" or "in response to detecting", depending on the context. Similarly, the phrases "if it is determined" or "if (stated condition or event) is detected" may be interpreted as "when it is determined" or "in response to determining" or "when detecting (stated condition or event)" or "in response to detecting (stated condition or event)", depending on the context.
[0128] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A fast-hardening high-strength cement anchor, characterized in that: Calculated by mass fraction, it includes the following raw materials: 50% to 70% sulphoaluminate cement, 10% to 20% silica fume, 10% to 20% desulfurized gypsum, 3% to 10% expansion agent, 0.05% to 0.3% composite retarder, 0.01% to 0.1% early strength agent, and 0.02% to 0.1% defoaming agent.
2. The fast-hardening high-strength cement anchoring agent according to claim 1, characterized in that: The composite retarder is sucrose and citric acid, or the composite retarder is borax and sodium citrate, or the composite retarder is a combination of sodium phosphate and phosphoric acid.
3. The fast-hardening high-strength cement anchoring agent according to claim 2, characterized in that: When the composite retarder is sucrose and citric acid, the mass ratio thereof is 4-4.5:1; when it is borax and sodium citrate, the mass ratio thereof is 10-15:1; when it is sodium phosphate and phosphoric acid, the mass ratio thereof is 4-4.5:
1.
4. The fast-hardening high-strength cement anchoring agent according to claim 1, characterized in that: The expansion agent is at least one of calcium oxide, sulphoaluminate or magnesium oxide expansion agents.
5. The fast-hardening high-strength cement anchoring agent according to claim 1, characterized in that: The early strength agent is ethylene glycol or diethanol monoisopropanolamine.
6. A strength testing method for the fast-hardening high-strength cement anchoring agent according to any one of claims 1 to 5, characterized in that: The steps include: S1: Collect the piezoresistive impedance signal data of cement anchor through piezoelectric ceramic sensor; S2: The rebound method collects the actual strength data of cement anchor at different strength stages; S3: preprocess the piezoelectric impedance signal dataset and the intensity dataset, and construct a time series dataset; S4: Use the long short-term memory network LSTM to train the model, learn the relationship between the piezoresistive impedance signal and the strength, and establish a cement anchor strength prediction model; S5: Validate and optimize the model; S6: Apply the optimized model to actual projects to achieve real-time nondestructive monitoring of cement anchor strength.
7. The strength testing method according to claim 6, characterized in that: In step S3, the specific steps include: S301: preprocessing the piezoelectric impedance signal, including performing empirical mode decomposition (EMD) and Hilbert transform (HHT) on the signal to extract the instantaneous amplitude; S302: Divide the processed signal data set into a training set and a validation set in proportion; S303: Label the data set to ensure that each signal data corresponds to the corresponding cement anchor strength.
8. The strength testing method according to claim 6, characterized in that: In step S5, the specific steps include: S501: Input the validation set into the trained model for prediction; S502: using a loss function to compare the intensity prediction result output by the model with the actual intensity; S503: Based on the comparison results, the weight parameters and network topology of the LSTM network are adjusted to optimize the model performance.
9. The strength testing method according to claim 8, characterized in that: In step S502, the mean square error (MSE) is used as a loss function to measure the error between the network predicted strength value and the true strength value. The formula is as follows: Among them, y i is the actual strength, Predict strength for the model.
Citation Information
Patent Citations
Cement free calcium soft measurement method based on multi-scale deep network
CN112365935A
Strength test method for cement solidified aeolian sand
CN114577602A
Quick-setting cement roll anchoring agent and preparation method thereof
CN114804789A
Full-process production method and system for intelligent integrated precast beam factory
CN117944173A
Physical engineering concrete compressive strength detection method based on regression algorithm
CN118050404A
Cited By
Method and system for testing compressive strength of bentonite slurry
CN122448663A